2011
DOI: 10.2478/s11658-011-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

ERp57/GRP58: A protein with multiple functions

Abstract: Abbreviations used: 1α,25-(OH) 2 D 3 -1α,25-dihydroxycholecalciferol and calcitriol; APE/Ref-1 -apurinic (apyrimidinic) endonuclease/redox-factor 1; CRP -C-reactive protein; ER -endoplasmic reticulum; ERAD endoplasmic reticulum associated protein degradation; mTORC -mammalian target of rapamycin complex; PDI -protein disulfide isomerase; PKC -protein kinases C; PLA 2 -phospholipases A 2 ; Plc -peptide loading complex; PLC -phospholipase C; PrP SC -scrapie prion protein (misfolded prions); STAT -signal transduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 86 publications
1
108
0
3
Order By: Relevance
“…72 ERp57 (GRP58) is a chaperone that regulated proper folding of glycoproteins. 73 ERp57 is associated with tumor progression ans has been described to modulate STAT 3 activity, thus regulating radioresistance in laryngeal cancer. 74 Accordingly, ERp57 has been described as a poor prognosis factor.…”
Section: Dna Damage Repair Biomarkersmentioning
confidence: 99%
“…72 ERp57 (GRP58) is a chaperone that regulated proper folding of glycoproteins. 73 ERp57 is associated with tumor progression ans has been described to modulate STAT 3 activity, thus regulating radioresistance in laryngeal cancer. 74 Accordingly, ERp57 has been described as a poor prognosis factor.…”
Section: Dna Damage Repair Biomarkersmentioning
confidence: 99%
“…Beside its role in the CNX and CRT cycle, ERp57 is required as a scaffold protein for the assembly of the heavy chain of the MHC class I peptide loading complex, a function independent of its enzymatic activity involving covalent bonding with tapasin (37-39). Additional functions for ERp57 are reported, including the modulation of ER calcium homeostasis and STAT3 signaling (34,40,41). Although PDIs have been proposed to have neuroprotective activities (30), a drug screening identified a proapoptotic role of ERp57 and PDIA1 in models of neurodegeneration (42).…”
mentioning
confidence: 99%
“…It was demonstrated recently that the amount of PDIA3 is reduced in the spermatozoa of male individuals with obesity-associated asthenozoospermia (Liu et al, 2015). Interestingly, PDIA3 also binds to the hydroxylated, hormonal form of vitamin D3,1a,25-dihydroxycholecalciferol (1a,25-(OH)2D3, calcitriol), and therefore may be involved in hormonal signaling processes (Nemere et al, 2004;Turano et al, 2011). This pathway activates numerous signal transduction cascades, such as protein kinase C (PKC), phospholipases C (PLC) and A2 (PLA2), and extracellular response activated kinase (ERK), all of which have been shown to respond to the formation of the PDIA3-1a,25-(OH)2D3 complex (Boyan et al, 2007;Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the main function of PDIA3 is to mediate the folding and quality control of newly synthesized glycoproteins in the endoplasmic reticulum (Coe & Michalak, 2010;Turano et al, 2011), it has also been found in other subcellular locations, such as in the nucleus, cytoplasm, and at the cell surface. Some studies have suggested that PDIA3 participates in transcriptional regulation (Coppari et al, 2002), signal transduction Ramirez-Rangel et al, 2011), membrane fusion (Schelhaas et al, 2007), hormone responses (Tunsophon & Nemere, 2010), and sperm-egg fusion (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%